How primary care can contribute to good mental health in adults*. Issue 1 (2nd January 2018) - Gupta, Sunjai; Jenkins, Rachel; Spicer, John; Marks, Marina; Mathers, Nigel; Hertel, Lise; Calamos Nasir, Laura; Wright, Fiona; Ruprah-Shah, Baljeet; Fisher, Brian; Morris, David; Stange, Kurt C.; et al.
Abstract: The need for support for good mental health is enormous. General support for good mental health is needed for 100% of the population, and at all stages of life, from early childhood to end of life. Focused support is needed for the 17.6% of adults who have a mental disorder at any time, including those who also have a mental health problem amongst the 30% who report having a long-term condition of some kind. All sectors of society and all parts of the NHS need to play their part. Primary care cannot do this on its own. This paper describes how primary care practitioners can help stimulate such a grand alliance for health, by operating at four different levels – as individual practitioners, as organisations, as geographic clusters of organisations and as policy-makers.